A strategy to speed up formation and strengthen activity of biofilms at low temperature. Issue 37 (26th April 2017) - Hu, Huizhi; He, Junguo; Yu, Huarong; Liu, Jian; Zhang, Jie
Abstract : The start-up period of biofilm reactors often takes a long time to obtain a mature and stable biofilm, especially at low temperature. Abstract : The start-up period of biofilm reactors often takes a long time to obtain a mature and stable biofilm, especially at low temperature. We performed a long-term study to investigate a strategy to improve biofilm formation and activity at low temperature (about 14 °C). A 25% increase in the speed of biofilm formation was observed with addition of a 50 nM N -acylhomoserine lactone (AHL) mixture, yielding a sustained increase of more than 20% in biofilm activity and pollutant removal, finally resulting in shortening the start-up phase. Enhanced bacterial attachment to the suspended carrier's surface was confirmed with confocal laser scanning microscopy (CLSM). The low level of polysaccharides (PS)/proteins (PN) at the end of biofilm formation with AHL addition also suggested that the effects of AHLs on PS production are more obvious than for PN. Analyses of the bacterial community by high-throughput sequencing showed a decrease in species diversity and a marked increase in most of the AHL-related microbial community members in an experimental reactor (ER). This work may offer a feasible approach to shorten the start-up phase of biofilm reactors and enhance biofilm performance at low temperature.